Execution of convictions for deprivation of liberty: Between the necessity for prompt execution and the requirements for postponement - BENTAHAR , Amina; BOUCETTA , Djamel (Journal of Human Sciences, 2025)
In an effort to realize the objectives of the criminal sanctions, modern laws have taken into account the penal provisions of executive rules and court controls to facilitate the completion of the procedure for their implementation in a complete manner, so as to achieve the essential equilibrium between the freedoms of other people who were harmed by the act and the interests of the condemned criminal as a human.It is in this context that the importance and necessity of prompt execution of convictions involving deprivation of liberty as a public asset has been emphasized in order to achieve the end of this penalty.